PEMBERIAN INSENTIF PENANAMAN MODAL SEBAGAI UPAYA DAYA TARIK INVESTASI DI DAERAH - Ahmad Zazili; Fathoni Fathoni; Ade Arif Firmansyah (University of Merdeka Malang, 2016)
Investment is an important element in the implementation of the economy in regions, that is as efforts to improve economic growth, create jobs, upgrading the development sustainable economic. Not easily attract an investor to invest in the required policies and strategies to attract investors. One policy that you can do is the policy of incentives investment (an investment). This study looked at a policy to invite the investors to invest in the form of investment; incentives that may be given investors to invest in the region. The methodology used normative study done by means of studying regulations be related to investment and legal products associated with local governments. The results showed first, the government has the authority to making policy incentives investment in regional policy; material incentives investment adjustable covering: tax deduction, tax relief, or exemption tax; reduction, lightning, or exemption retribution; fund stimulant; the capital assistance.